Modeling shrimp biomass and viral infection for production of biological countermeasures - H. Thomas Banks; V. A. Bokil; Shuhua Hu; A. K. Dhar; R. A. Bullis; C. L. Browdy; F.C.T. Allnutt (Mathematical Biosciences and Engineering)
In this paper we develop a mathematical model for the rapid productionof large quantities of therapeutic and preventive countermeasures. Wecouple equations for biomass production with those for vaccine production inshrimp that have been infected with a recombinant viral vector expressing aforeign antigen. The model system entails both size and class-age structure.